Herbicide Selectivity in Tropical Ornamental Species - QUEIROZ,J.R.G. (2016)
ABSTRACT This study evaluated the selectivity of herbicides applied post-emergence on ornamental plants of Alpinia purpurata, Strelitzia reginae and Heliconia psittacorum. The study was conducted in two seasons. The experimental design was completely randomized with four replications. The treatments were: fluazifop-p-butyl (87.5 g ha-1), quizalofop-p-ethyl (75.0 g ha-1), sethoxydim (184.0 g ha-1), quinclorac (375.0 g ha-1), chlorimuron-ethyl (15.0 g ha-1), clethodim + fenoxaprop-p-ethyl (37.5 + 37.5 g ha-1), bentazon (720.0 g ha-1), fomesafen (225.0 g ha-1), and a control without any herbicide. In general, all tested herbicides and doses were selective for the three studied species. Although plants of A. purpurata and H. psittacorum have shown symptoms of phytotoxicity, recovery occurred with subsequent satisfactory visual appearance at the end of the evaluations. However, the S. reginae plants showed the smallest dry mass values when the sethoxydim and quizalofop-p-ethyl herbicides were sprayed.